જો ${a^x} = {b^y} = {(ab)^{xy}},$ તો $x + y = $
$0$
$1$
$xy$
એકપણ નહીં
જો $x \ne 0 $ તો ${\left( {{{{x^l}} \over {{x^m}}}} \right)^{({l^2} + lm + {m^2})}}$${\left( {{{{x^m}} \over {{x^n}}}} \right)^{({m^2} + nm + {n^2})}}{\left( {{{{x^n}} \over {{x^l}}}} \right)^{({n^2} + nl + {l^2})}}=$
$\sqrt {[12 - \sqrt {(68 + 48\sqrt 2 )} ]} = $
જો $x = {{\sqrt 5 + \sqrt 2 } \over {\sqrt 5 - \sqrt 2 }},y = {{\sqrt 5 - \sqrt 2 } \over {\sqrt 5 + \sqrt 2 }},$ તો $3{x^2} + 4xy - 3{y^2} = $
જો ${a^{1/x}} = {b^{1/y}} = {c^{1/z}}$ અને ${b^2} = ac$ તો $x + z = $
જો ${a^x} = bc,{b^y} = ca,\,{c^z} = ab,$ તો $xyz=$